Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 581289 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Chlorophyta" ] } The dataset includes 581289 records from 474 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001247-150504100648427/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences